Pieties and gender - Christensen, Hilda Rømer.; Sjørup, Lene. (International Studies in Religion and Society, 2009)
Taking up the challenge of Saba Mahmood to feminist studies in religion, that there is a liberalist understanding of agency and a tendency to mix the feminist political project with the analytical, the authors of this anthology discuss the relations between pieties and politics, pieties and methodologies, virtuous masculinities, and symbolic gender representations. Several articles discuss highly controversial questions: Muslim piety, religion in the European Union between the Vatican and the Muslim populations, the religiously motivated abstinence policies of the US. Furthermore, there is an interesting section about religious masculinities in a historical and contemporary perspective.